Influence of deposition temperature on WTiN coatings tribological performance (2017)
WTiN films were grown on silicon and stainless-steel substrates using the DC magnetron sputtering technique. The substrate temperature was varied taking values of 100 °C, 200 °C, 300 °C, and 400 °C. X-ray diffraction analysis allowed us to identify a rock salt-type face centered cubic (FCC) structure, with a lattice parameter of approximately 4.2 nm, a relatively low microstrain (deformations at microscopy level, between 4.7% and 6.7%), and a crystallite size of a few nanometers (11.6 nm–31.5 nm). The C1s, N1s, O1s, Ti2p, W4s, W4p, W4d and W4f narrow spectra were obtained using X-ray photoelectron spectroscopy (XPS) and depending on the substrate temperature, the deconvoluted spectra presented different binding energies. Grain sizes and roughness (approximately 4 nm) of films were determined using atomic force microscopy. Scratch and pin on disc tests were conducted, showing better performance of the film grown at 200 °C. This sample exhibited a lower roughness, coefficient of friction, and wear rate. © 2017